FY2018 Ecuador Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Ecuador assists the World Bank Group (WBG) in gaining abetter understanding of how stakeholders in Ecuador perceive the WBG. It provides the WBGwith systematic feedback from national and local governments, multilateral/bilateral agencies,media, academia, the private sector, and civil society in Ecuador on 1) their views regarding thegeneral environment in Ecuador; 2) their overall attitudes toward the WBG in Ecuador; 3)overall impressions of the WBG’s effectiveness and results, knowledge work and activities, andcommunication and information sharing in Ecuador; and 4) their perceptions of the WBG’sfuture role in Ecuador.